A Modular System for Treating Moving Anatomical Targets With Scanned Ion Beams at Multiple Facilities: Pre-Clinical Testing for Quality and Safety of Beam Delivery - Lis, Michelle; Newhauser, Wayne; Donetti, Marco; Wolf, Moritz; Steinsberger, Timo; Paz, Athena; Durante, Marco; Graeff, Christian (Frontiers in Oncology, 2021)
Background: Quality management and safety are integral to modern radiotherapy. New radiotherapy technologies require new consensus guidelines on quality and safety. Established analysis strategies, such as the failure modes and effects analysis (FMEA) and incident learning systems have been developed as tools to assess the safety of several types of radiation therapies. An extensive literature documents the widespread application of risk analysis methods to photon radiation therapy. Relatively little attention has been paid to performing risk analyses of nascent radiation therapy systems to treat moving tumors with scanned heavy ion beams. The purpose of this study was to apply a comprehensive safety analysis strategy to a motion-synchronized dose delivery system (M-DDS) for ion therapy. Methods: We applied a risk analysis method to new treatment planning and treatment delivery processes with scanned heavy ion beams. The processes utilize a prototype, modular dose delivery system, currently undergoing preclinical testing, that provides new capabilities for treating moving anatomy. Each step in the treatment process was listed in a process map, potential errors for each step were identified and scored using the risk probability number in an FMEA, and the possible causes of each error were described in a fault tree analysis. Solutions were identified to mitigate the risk of these errors, including permanent corrective actions, periodic quality assurance (QA) tests, and patient specific QA (PSQA) tests. Each solution was tested experimentally. Results: The analysis revealed 58 potential errors that could compromise beam delivery quality or safety. Each of the 14 binary (pass-or-fail) tests passed. Each of the nine QA and four PSQA tests were within anticipated clinical specifications. The modular M-DDS was found to function, without modification, at two centers. Conclusion: We have applied a comprehensive risk analysis strategy to the M-DDS and shown that it is a clinically viable motion mitigation strategy. The described strategy can be utilized at any ion therapy center that operates with the modular M-DDS. The approach can also be adapted for use at other facilities and can be combined with existing safety analysis systems.